2012
DOI: 10.1016/j.diff.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-retinoid acid induces the differentiation of encapsulated mouse embryonic stem cells into GABAergic neurons

Abstract: Embryonic stem (ES) cells are pluripotent cells that can differentiate into all three main germ layers: endoderm, mesoderm, and ectoderm. Although a number of methods have been developed to differentiate ES cells into neuronal phenotypes such as sensory and motor neurons, the efficient generation of GABAergic interneurons from ES cells still presents an ongoing challenge. Because the main output of inhibitory GABAergic interneurons is the gamma-aminobutyric-acid (GABA), a neurotransmitter whose controlled home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…It will be interesting to study if different type of primary neuron culture should be used to generate specific neurons subtype. The capability of our hNPs to differentiate in different subtypes of neurons is confirmed by the ability of retinoic acid to induce the maturation of inhibitory neurons (Addae et al, 2012). The differentiation potential of these cells into glial cells has been also determined (data not shown).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…It will be interesting to study if different type of primary neuron culture should be used to generate specific neurons subtype. The capability of our hNPs to differentiate in different subtypes of neurons is confirmed by the ability of retinoic acid to induce the maturation of inhibitory neurons (Addae et al, 2012). The differentiation potential of these cells into glial cells has been also determined (data not shown).…”
Section: Discussionmentioning
confidence: 57%
“…Thus, in order to improve the differentiation of GABAergic neurons, we plated EGFP-hNPs onto rat cortical neurons as previously described and treated the coculture with 1μ M retinoic acid starting 24 h after plating (Addae et al, 2012). After 60 days of differentiation, we stained the hNP-derived mature neuronal cells using an anti-GAD67 antibody to detect GABAergic neurons and observed a MAP2, GAD67, and VGAT positive population of cells (Figures 6A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Encapsulated cells are buffered in vivo from external factors such as antibodies from the host (Serra et al, ). Furthermore, it has been shown that the alginate encapsulation promotes cell growth, differentiation, maturation, and protein secretion of various cell types including mesenchymal stem cells, mouse ESCs, and human ESCs (Addae et al, ; Serra et al, ). Despite success in the growth support of many cell types, studies utilising alginate encapsulation for hiPSC differentiation and 3D culture are limited (Addae et al, ; Chayosumrit et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Undifferentiated ES cells were maintained on gelatin-coated dishes in ES medium (Dulbecco’s Modified Eagle medium supplemented with 10% ES qualified fetal calf serum (Atlanta Biologicals) as previously described (Addae et al, 2012). In addition, 1 × 10 3 U/ml leukemia inhibitory factor (LIF, Esgro, Millipore) was added to the medium.…”
Section: Methodsmentioning
confidence: 99%